2007
DOI: 10.3892/ijo.31.4.761
|View full text |Cite
|
Sign up to set email alerts
|

Cepharanthin-enhanced radiosensitivity through the inhibition of radiation-induced nuclear factor-κB activity in human oral squamous cell carcinoma cells

Abstract: We have already demonstrated that human head and neck cancer cells have significantly enhanced levels of transcription factor nuclear factor (NF)-κB activity compared to their normal counterparts, suggesting that NF-κB plays an important role in the development of head and neck cancer. However, it has been reported that chemotherapeutic agents and radiation activate NF-κB activity in cancer cells, thus making the cells radioresistant and chemoresistant. In addition, we have shown that the suppression of NF-κB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…The understanding of apoptosis process has provided the basis for novel, targeted therapies that specifically induce cell death in carcinoma cell lines or enhance the cytotoxic effects of established chemotherapeutic agents in these cells [29]. Ability to manipulate the machinery of cell death is an obvious goal of medical research and effect on regulation of apoptosis might lead to new possibilities for cancer treatment [30]. It is well documented that the secondary metabolites of Sinularia sps have induced apoptotic DNA fragmentation and condensation of chromatin in A431 cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of apoptosis process has provided the basis for novel, targeted therapies that specifically induce cell death in carcinoma cell lines or enhance the cytotoxic effects of established chemotherapeutic agents in these cells [29]. Ability to manipulate the machinery of cell death is an obvious goal of medical research and effect on regulation of apoptosis might lead to new possibilities for cancer treatment [30]. It is well documented that the secondary metabolites of Sinularia sps have induced apoptotic DNA fragmentation and condensation of chromatin in A431 cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory pathways that are important in carcinogenesis include NF-κB, STATs and COX -, and they are promising targets for cancer therapy [31,32] . Previous studies have shown that inactivation of NF-κB is an important mechanism for the antitumor activity of CEP [8,15,16] . SaOS2 is an osteosarcoma cell line in which STAT3 is constitutively activated and plays a crucial role in cell proliferation and survival [10,22,33] .…”
Section: Discussionmentioning
confidence: 99%
“…Although accumulating evidence has shown that CEP plays a potential role in inhibiting cell growth and inducing apoptosis in many tumors [3] , the underlying mechanism remains elusive. Because CEP is primarily an anti-inflammatory agent, the antitumor activity of CEP is associated with inhibition of inflammation-related signaling pathways, among which NF-κB inactivation is important [8,15,16] . In addition to NF-κB, the signal transducer and activator of transcription protein 3 (STAT3) is another critical inflammatory mediator that links inflammation and cancer [17] .…”
Section: Introductionmentioning
confidence: 99%
“…39 It was recently reported that Cep sensitizes human oral carcinoma cells to radiation by inhibiting activation of NFκB. 55 As mentioned, the NFκB is the most likely target of Onc as well. 28 In analogy to Cep Onc also shows antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%